ANALISIS PERGESERAN PENGGUNAAN BAHASA BUGIS DIALEK BARRU DI KOTA MAKASSAR (KAJIAN SOSIOLINGUISTIK) - Musyawir, Musyawir; Rifta Wabula; Fitria Lapandewa; Sitra Rumra; Nurhikmah, Nurhikmah (Bajang Institute, 2025)
This study aims to describe objectively and clearly the shift in the use of the Bugis Barru dialect in Makassar City in a sociolinguistic study. This type of research is qualitative research. The data in this study are in the form of speech by Bugis Barru dialect speakers in Makassar City and data sources from Bugis Barru dialect speakers. Furthermore, the data collection techniques for this study are observation, interviews, and documentation using qualitative analysis as a data analysis technique. The data that has been collected is then analyzed by identifying data based on the focus of the problem and the purpose of the study. The results of the study show that the shift in the use of the Bugis Barru dialect in Makassar City has shifted and the speakers are more dominant in using Indonesian than the Bugis Barru dialect.